2014
DOI: 10.1111/trf.12923
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of plasmapheresis on donor‐specific antibody reduction by HLA specificity in post–kidney transplant recipients

Abstract: BACKGROUND Donor-specific antibodies (DSAs) to HLA antigens can cause acute antibody-mediated rejection (AMR) after kidney transplantation (Txp). Therapeutic plasma exchange (TPE) has been used for AMR treatment; however, DSA reduction rates are inconsistent. We investigated DSA reduction rates by HLA specificity and clinical outcome. STUDY DESIGN AND METHODS Sixty-four courses of TPE for 56 kidney Txp recipients with high DSA were investigated. Dates of TPE procedures and Txp, patients’ age, sex, race, crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 37 publications
3
41
0
4
Order By: Relevance
“…Our cases show that 1 course of 5–6 TPE treatment, followed by IVIG, successfully reduces AT1RAb level by 20.0% and 55.6%, median 37.8%. This rate is similar to the reduction rates of HLA DSA in kidney transplant recipients with AMR that we previously reported elsewhere . However, the effect of TPE was temporally and AT1RAb rebound and increase over the time were also observed, which indicates that follow‐up of these patients is critical.…”
Section: Discussionsupporting
confidence: 89%
“…Our cases show that 1 course of 5–6 TPE treatment, followed by IVIG, successfully reduces AT1RAb level by 20.0% and 55.6%, median 37.8%. This rate is similar to the reduction rates of HLA DSA in kidney transplant recipients with AMR that we previously reported elsewhere . However, the effect of TPE was temporally and AT1RAb rebound and increase over the time were also observed, which indicates that follow‐up of these patients is critical.…”
Section: Discussionsupporting
confidence: 89%
“…While the duration of TPE for the treatment of AMR is dictated by the clinical response and/or antibody level, an ideal protocol is not yet known—a common TPE schedule involves reassessment for a response after five TPEs approximately every other day . In one study, for 56 patients with elevated DSAs treated with an average of six TPEs (to avoid DSA rebound), outcomes tended to be better if the treatments occurred within the first year after transplant compared to after 1 year, although this was not significant . In addition, there were more DSAs found to HLA Class II as compared to HLA Class I antigens (84% vs. 66%) …”
Section: Resultsmentioning
confidence: 99%
“…In one study, for 56 patients with elevated DSAs treated with an average of six TPEs (to avoid DSA rebound), outcomes tended to be better if the treatments occurred within the first year after transplant compared to after 1 year, although this was not significant . In addition, there were more DSAs found to HLA Class II as compared to HLA Class I antigens (84% vs. 66%) …”
Section: Resultsmentioning
confidence: 99%
“…Despite these biopsy results, DSA rebound was observed with the class I DSA that initially responded and treatment resistance was observed in class II DSA titers . Yamada et al found DSA class II MFI rebound in their cohort of 56 kidney transplant patients who received four to six PP sessions for AMR treatment. Contrary to previous reports, we observed a sustained reduction in DSA MFI across both classes out to 24 months (when available), so treatment was not associated with a rebound effect.…”
Section: Discussionmentioning
confidence: 97%